2022
DOI: 10.3390/biomimetics7040149
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Electrospinning in Liver Tissue Engineering

Abstract: The major goal of liver tissue engineering is to reproduce the phenotype and functions of liver cells, especially primary hepatocytes ex vivo. Several strategies have been explored in the recent past for culturing the liver cells in the most apt environment using biological scaffolds supporting hepatocyte growth and differentiation. Nanofibrous scaffolds have been widely used in the field of tissue engineering for their increased surface-to-volume ratio and increased porosity, and their close resemblance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…Such scaffolds have advantages for tissue engineering, such as promoting cell adhesion, proliferation, migration, and differentiation [ 124 ]. Many natural and synthetic polymers produce scaffolds in skin tissue engineering [ 125 , 126 , 127 ]. Scientists produced many biodegradable polymers to transport pharmaceuticals, macromolecules, cells, and enzymes into the body [ 34 ].…”
Section: Biodegradable and Nondegradable Polymers For Wound Healingmentioning
confidence: 99%
“…Such scaffolds have advantages for tissue engineering, such as promoting cell adhesion, proliferation, migration, and differentiation [ 124 ]. Many natural and synthetic polymers produce scaffolds in skin tissue engineering [ 125 , 126 , 127 ]. Scientists produced many biodegradable polymers to transport pharmaceuticals, macromolecules, cells, and enzymes into the body [ 34 ].…”
Section: Biodegradable and Nondegradable Polymers For Wound Healingmentioning
confidence: 99%
“…PLA and PLLA also have had various attempts to support the viability and function of liver cells [ 33 , 94 ]. It has been reported that hepatocytes grow well when fetal liver cells are cultured on a 3D printed PLLA scaffold.…”
Section: Advantages Of 3d Cultures In Studies On the Liver Metabolismmentioning
confidence: 99%
“…Electrospinning is the most appropriate technique to fabricate nanoscaffolds because nanofibers produced as a result of electrospinning closely mimic the dense collagen network of the tissue ECM . Electrospinning also offers user-defined scaffold fabrication with tunable pore sizes. , Nanofiber scaffolds provide a high surface-to-volume ratio, with an ability to incorporate more cells in limited space . The diameter of nanofiber scaffolds provides an optimum spatial arrangement suitable for integrin binding of the cells .…”
Section: Introductionmentioning
confidence: 99%